Geometric morphometrics of wing venation to differentiates new species of Scaura Schwarz populations (Hymenoptera: Apidae: Meliponini) - Nogueira, David Silva; Mahlmann, Thiago; Teixeira, Juliana Stephanie Galaschi; Oliveira, Marcio Luiz de; Roubik, David Ward (Scientia Plena, 2019)
Scaura Schwarz, 1938 is a small Neotropical genus of stingless bees widely distributed in Brazil. The new species of Scaura is a widespread species, and its wide distribution may suggest that it is a species complex. In order to differentiate populations that could compose cryptic species, we studied the wing venation variation using geometric morphometrics in 56 workers, 23 of these from remaining of Atlantic Forest in Ceará state and 33 from the Amazon region. Bees from Atlantic Forest differed of the bees from Amazon region, corresponding to 38.05% of total variation (principal components analysis), 100% of canonical variation and 52.93% of canonical variation between localities, with significant difference between populations in discriminant function analysis (p<0.001). The results suggest that the Atlantic Forest bees may be a new species. However, it is necessary more detailed morphological studies, and/or a molecular analysis to confirm this possibility.